EFFECTS OF RENEWABLE INVESTMENT AND EXCHANGE RATE ON SUSTAINABLE DEVELOPMENT IN NIGERIA (Journal of the Management Sciences, 2026)
Inability to effectively adapt to climate change and transit at the necessary speed is a major challenge for developing countries. In Nigeria, the rising population has escalated energy demands. However, the country is endowed with substantial renewable resources that remain largely untapped for sustainable development. This study, investigated the effect of renewable investment (RI) and exchange rate (ER) on two sustainable development goals (child mortality and CO2 emission reduction) from 2000 to 2023.  Among others, the study used the Autoregressive Distributed Lag (ARDL) long and short run forms technique to estimate the effect of renewable investment variables, namely renewable energy investment (REIV) and renewable investment in agriculture and afforestation (RAIV) and foreign exchange rates, namely nominal effective exchange rate (NEER) and real exchange rate (REER) on sustainable development indicators, under 5 child mortality rate (MORT) and CO2 emission (CO2E). In the short run, the ARDL results show that LOGRAIV has a significant negative effect on MORT (coefficient = -1.816061; p = 0.0343), NEER has a significant negative effect on MORT (coefficient = -0.009240; p = 0.0005).  There was no significant relationship between any of RI and ER variables on MORT in the long run. On CO2 emission, LOGREIV has a significant negative impact (coefficient = -2.364818, p = 0.0000) in the short run and NEER exerted a negative and significant effect on LOGCO2E (coeff = -0.000254, p = 0.0170). In the long run, LOGREIV has a negative and significant effect on LOGCO2E (-4.189907, p = 0.0081).  Additionally, LOGRAIV significantly reduced LOGCO2E, with a coefficient of -0.614177 (p = 0.0384). Based on these findings, we conclude that RI and ER have greater effect on sustainable development in the short run than in the long run. It is hereby recommended that Nigerian governments should continue to prioritize and increase investments in renewable energy, ensure stable exchange rate, and sustainable agricultural practices, thereby developing robust policy frameworks to integrate renewable energy and sustainable agriculture into broader economic and environmental strategies which will drive sustainable development.
Keywords: Renewable Investment; Exchange Rate; Sustainable Development; ARDL; CO2 Emission; Renewable Energy